Zaid ibn Haritha story in the Qur'an between the construction of narrative and knowledge systemic  - BEN SAGHRI, ZOUBIRE (Milev Journal of Research and Studies, 2015)
A lot of studies appeared which are interested of Koran text language on all voice and semantic and syntactic levels, lexical and rhetorical and every feature, including mowing the Quranic that appeared as a cognitive and linguistic in most of the verses of the Qur'an in the lengths and clips narrative different from the ferry and the reference to the full building stories. We'll give importance the relationship of narrative forms of knowledge; that is why the revealed knowledge of God in this form narrative was inflicted in the form of abstract, direct and simple terms, is the content of cognitive story differs from other linguistic forms of direct speech and dialogue and story, this cognitive pattern was repeated in all the heavenly texts. In addition to the above Does God Almighty reference to some texts by the shear sufficient indication that the story in the Koran is literary or is it a historical drop of human knowledge on those language features